2019
DOI: 10.4049/jimmunol.1800242
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Clinical Impact of the Immunologic Tumor Microenvironment in Oral Squamous Cell Carcinoma

Abstract: Immunotherapy shows promising results and revolutionizes treatment of oral squamous cell carcinoma (OSCC). The immunologic microenvironment might have prognostic/predictive implications. Morphologic immunologic parameters (inflammatory infiltrate, stromal content, and budding activity [BA] [potentially indicating epithelial–mesenchymal transition]) were evaluated in 66 human primary therapy-naive OSCCs. Intraepithelial/stromal tumor-infiltrating lymphocytes (TILs; CD3+/CD4+/CD8+/CD4+FOXP3+/IL-17A+) were quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 64 publications
7
56
0
Order By: Relevance
“…Additionally, the current study also identified that a high CD8/CD4 ratio was associated with better DMFS and LRFS in UVA and was an independent prognostic factor for LRFS in MVA, although CD4 infiltrating T cells alone were not significantly correlated with survival implications. Consistent with our results, previous studies have reported that a high stromal CD8/CD4 ratio was found to be an independent favourable prognostic factor in oral squamous cell carcinoma, and one study revealed that the CD8/CD4 ratio was higher in cases without metastasis and in low-grade lesions [42,43]. Moreover, studies in lung cancer suggested that the CD8/ CD4 ratio in patients in the non-metastasis group was remarkably higher, and these patients had a significantly better overall survival rate than patients with a low CD8/ CD4 ratio [44,45].…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, the current study also identified that a high CD8/CD4 ratio was associated with better DMFS and LRFS in UVA and was an independent prognostic factor for LRFS in MVA, although CD4 infiltrating T cells alone were not significantly correlated with survival implications. Consistent with our results, previous studies have reported that a high stromal CD8/CD4 ratio was found to be an independent favourable prognostic factor in oral squamous cell carcinoma, and one study revealed that the CD8/CD4 ratio was higher in cases without metastasis and in low-grade lesions [42,43]. Moreover, studies in lung cancer suggested that the CD8/ CD4 ratio in patients in the non-metastasis group was remarkably higher, and these patients had a significantly better overall survival rate than patients with a low CD8/ CD4 ratio [44,45].…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, the current study also identi ed that a high CD8/CD4 ratio was associated with better DMFS and LRFS in UVA and was an independent prognostic factor for LRFS in MVA, although CD4 in ltrating T cells alone were not signi cantly correlated with survival implications. Consistent with our results, previous studies have reported that a high stromal CD8/CD4 ratio was found to be an independent favourable prognostic factor in oral squamous cell carcinoma, and one study revealed that the CD8/CD4 ratio was higher in cases without metastasis and in low-grade lesions [42,43]. Moreover, studies in lung cancer suggested that the CD8/CD4 ratio in patients in the non-metastasis group was remarkably higher, and these patients had a signi cantly better overall survival rate than patients with a low CD8/CD4 ratio [44,45].…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our data, Boxberg et al . reported that low density of FOXP3 + TILs significantly correlated with inferior survival in OSCC . In addition, high FOXP3 + TILs tended to associate with increased survival in HPV‐ oral cancer, although p values did not reach statistical significance .…”
Section: Discussionmentioning
confidence: 95%
“…44,45 Consistent with our data, Boxberg et al reported that low density of FOXP3 + TILs significantly correlated with inferior survival in OSCC. 46 In addition, high FOXP3 + TILs tended to associate with increased survival in HPV-oral cancer, although p values did not reach statistical significance. 21 Some have proposed that the prognostic roles of FOXP3 + TILs are highly influenced by tumor sites, molecular subtypes and stages of tumor.…”
Section: Locations and Densities Of Seven Tiis Subpopulations In Osccmentioning
confidence: 91%